The dynamic cycle of bacterial translation initiation factor IF3 - Nakamoto, Jose A. (2021)
InnovatePeru [382-PNICP-PIBA-2014 and 297INNOVATEPERU-EC-2016 to P.M.]; Fondo Nacional de Desarrollo Cientifico, Tecnologico y de Innovacion Tecnologica [154-2017-Fondecyt and 0362019-Fondecyt-BM-INC.INV to P.M.]; FIRB Futuro in Ricerca [RBFR130VS5 001 to A.F.]; Italian Ministero dell'Istruzione, dell'Universita e della Ricerca (to A.F.); Part of the work on structural dynamics of the ribosome was supported by Russian Science Foundation [17-1401416 to A.L.K.]. Funding for open access: Universidad Peruana de Ciencias Aplicadas (Exp-03).